A cross‐sectional study of SARS‐CoV‐2 seropositivity among healthcare workers and residents of long‐term facilities in Italy, January 2021. Issue 7 (6th March 2022) - Bordino, Valerio; Marengo, Noemi; Garlasco, Jacopo; Cornio, Alessandro Roberto; Meddis, Davide; Ditommaso, Savina; Giacomuzzi, Monica; Memoli, Gabriele; Gianino, Maria Michela; Vicentini, Costanza; Zotti, Carla Maria; ,
Abstract: Long‐term care facilities (LTCFs) are high‐risk settings for SARS‐CoV‐2 infection. This study aimed to describe SARS‐CoV‐2 seropositivity among residents of LTCFs and health‐care workers (HCWs). Subjects were recruited in January 2021 among unvaccinated HCWs of LTCFs and hospitals and residents of LTCFs in Northern Italy. Information concerning previous SARS‐CoV‐2 infections and a sample of peripheral blood were collected. Anti‐S SARS‐CoV‐2 IgG antibodies were measured using the EUROIMMUN Anti‐SARS‐CoV‐2 QuantiVac ELISA kit (EUROIMMUN Medizinische Labordiagnostika AG). For subjects with previous COVID‐19 infection, gender, age, type of subject (HCW or resident), and time between last positive swab and blood draw were considered as possible determinants of two outcomes: the probability to obtain a positive serological result and antibody titer. Six hundred and fifty‐eight subjects were enrolled. 56.1% of all subjects and 65% of residents presented positive results (overall median antibody titer: 31.0 RU/ml). Multivariable models identified a statistically significant 4% decrease in the estimated antibody level for each 30‐day increase from the last positive swab. HCWs were associated with significant odds for seroreversion over time (OR: 0.926 for every 30 days, 95% CI: 0.860–0.998), contrary to residents (OR: 1.059, 95% CI: 0.919–1.22). Age and gender were not factors predicting seropositivity over time. Residents could have a higher probability of maintaining a seropositive status over time compared to HCWs.